2023
DOI: 10.3390/met13071226
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Microstructure and Mechanical Properties of Layered Material Produced by Adding Al2O3 to 316L Stainless Steel

Osama Albahl Alshtewe Albahlol,
Rajab Elkilani,
Harun Çuğ
et al.

Abstract: This study developed new advanced composite materials consisting of functional grading of 316L and Al2O3 specially designed for potential biomedical applications. Mechanical properties were characterized by tensile testing, and microstructural properties by optical microscope, scanning electron microscope (SEM), and Energy Dispersive X-Ray (EDX) analyses. The uniform mixture in the material, up to 40% by weight of Al2O3, is uniformly distributed in the 316L matrix that shows disintegration. Then, samples with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The authors reported that microhardness increased for all alloy compositions, tensile strength decreased, and compressive strength increased for the alloy containing equal concentrations of niobium and titanium additions. Albahlol et al [14] examined the influence of Al 2 O 3 addition on the microstructure and mechanical characteristics of 316 L stainless steel. Their findings revealed that it is possible to create novel composite materials by layering 316 L and Al 2 O 3 , and that these materials are well-suited for application as alternative prosthetic materials in the field of biomedical engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that microhardness increased for all alloy compositions, tensile strength decreased, and compressive strength increased for the alloy containing equal concentrations of niobium and titanium additions. Albahlol et al [14] examined the influence of Al 2 O 3 addition on the microstructure and mechanical characteristics of 316 L stainless steel. Their findings revealed that it is possible to create novel composite materials by layering 316 L and Al 2 O 3 , and that these materials are well-suited for application as alternative prosthetic materials in the field of biomedical engineering.…”
Section: Introductionmentioning
confidence: 99%